A study of coupled magnetic fields for an optimum torque generation - Mohd Suhadis, Nurulasikin; Varatharajoo, Renuganth (International Society of Multiphysics, 2012)
Magnetic torquers are specifically designed to generate a magnetic field onboard the satellites for their attitude control. A control torque is generated when the magnetic fields generated by the magnetic torquers couple with the geomagnetic fields, whereby the vector of the generated torque is perpendicular to both the magnetic fields. In this paper, two control algorithms for a momentum bias satellite implementing two and three magnetic torquers onboard have been developed. The structured algorithms are for an optimum torque generation and eventually controlling the satellite attitudes (roll/yaw) and nutation using a proportional (P) controller as well as managing the excess angular momentum via a proportional-integral (PI) controller. The developed control algorithms were tested using the complex and simplified geomagnetic field models for a LEO satellite mission in a nominal attitude operation. Their attitude torque generation performances were compared and it is found that the optimum torques can be generated by both the developed control algorithms. However, the system with three magnetic torquers provides a better torque generation compartment and consequently gives a better attitude performance up to 0.5 deg.